Further medical experience will be required to validate these results: How experience -based medicine shapes the validity of medical evidence. Issue 1 (February 2020) - Bagli, Darius; Herbst, Katherine W.; Harper, Luke; Beckers, Goedele; Kaefer, Martin; Kalfa, Nicolas; Fossum, Magdalena
Abstract: This communication contextualizes the importance of clinical experience or experience-based medicine within the current paradigm of evidence-based medicine, complementing our previously published series of five short educational articles on evidence-based medicine. Previously we focused on optimizing medical decisions using publications of well-conducted research. Previous commentaries included a backgrounder, the hierarchy of evidence, data acquisition, tools for critical appraisal, and clinical use of evidence based medicine.